2012
DOI: 10.1017/s1366728912000090
|View full text |Cite
|
Sign up to set email alerts
|

The measure matters: Language dominance profiles across measures in Spanish–English bilingual children

Abstract: The purpose of this study was to determine if different language measures resulted in the same classifications of language dominance and proficiency for a group of bilingual pre-kindergarteners and kindergarteners. Data were analyzed for 1029 Spanish–English bilingual pre-kindergarteners who spanned the full range of bilingual language proficiency. Parent questionnaires were used to quantify age of first exposure and current language use. Scores from a short test of semantic and morphosyntactic development in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
251
2
15

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 276 publications
(322 citation statements)
references
References 68 publications
27
251
2
15
Order By: Relevance
“…The extant literature provides robust evidence that relative language exposure is an important source of variability for bilingual language proficiency (Bedore et al, 2012;David & Wei, 2008;Eilers, Pearson, & Cobo-Lewis, 2006;Pearson, Fernandez, Lewedeg, & Oller, 1997;Place & Hoff, 2011;Poulin-Dubois, Bialystok, Blaye, Polonia & Yott, 2013). However, assessment of relative language exposure in bilingual infants and children who are unable to report on their language experience presents a unique problem for researchers and clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…The extant literature provides robust evidence that relative language exposure is an important source of variability for bilingual language proficiency (Bedore et al, 2012;David & Wei, 2008;Eilers, Pearson, & Cobo-Lewis, 2006;Pearson, Fernandez, Lewedeg, & Oller, 1997;Place & Hoff, 2011;Poulin-Dubois, Bialystok, Blaye, Polonia & Yott, 2013). However, assessment of relative language exposure in bilingual infants and children who are unable to report on their language experience presents a unique problem for researchers and clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Because language proficiency and language ability are difficult to disambiguate in a sample of children with potential SLI, we determined language dominance on the basis of detailed parent and teacher interviews of children's language exposure and use (Gutierrez-Clellen & Kreiter, 2003). Language exposure, use, and history are highly related to children's language performance (Pearson, Fernández, Lewedeg, & Oller, 1997), but the nature of the relationship varies by domain (Bedore et al, 2012;Bohman et al, 2010). Thus, our approach enabled evaluation of language performance across children relative to their linguistic environment.…”
Section: The Longitudinal Portion Of the Studymentioning
confidence: 99%
“…However, they were only more successful in correctly interpreting bare NPs and not definite NPs. Several studies have found that variations in the input play a role in the rate of acquisition of child L2 learners [26,27] and bilingual children [28][29][30][31][32]. Variation in the input can have an effect on the morphosyntactic domain as well as on the semantic domain [28].…”
Section: Discussionmentioning
confidence: 99%